Characterization of xylitol-utilizing mutants of Erwinia uredovora. - Doten, R C (1985)
Of the four pentitols ribitol, xylitol, D-arabitol, and L-arabitol, Erwinia uredovora was able to utilize only D-arabitol as a carbon and energy source. Although attempts to isolate ribitol- or L-arabitol-utilizing mutants were unsuccessful, mutants able to grow on xylitol were isolated at a frequency of 9 X 10(-8). Xylitol-positive mutants constitutively synthesized both a novel NAD-dependent xylitol-4-dehydrogenase, which oxidized xylitol to L-xylulose, and an L-xylulokinase. The xylitol dehydrogenase had a Km for xylitol of 48 mM and showed best activity with xylitol and D-threitol as substrates. However, D-threitol was not a growth substrate for E. uredovora, and its presence did not induce either dehydrogenase or kinase activity. Attempts to determine the origin of the xylitol catabolic enzymes were unsuccessful; neither enzyme was induced on any growth substrate or in the presence of any polyol tested. Analysis of xylitol-negative mutants isolated after Tn5 mutagenesis suggested that the xylitol dehydrogenase and the L-xylulokinase structural genes were components of two separate operons but were under common regulatory control.